"Through the looking glass: envisioning new library technologies" future of energy, transportation and place. Issue 6 (6th June 2022) - Fernandez, Peter
Abstract : Purpose: Understanding the environmental motivations that shape these technological developments as well as how they interact with network effects will position libraries to create services and spaces that can thrive as transportation evolves.  Design/methodology/approach: This column explores a series of interrelated emerging technologies that are poised to transform how libraries relate to the space around them. Findings: As electronic vehicles and autonomous vehicles continue to transform the landscape, the decisions libraries make today will have reverberations in the coming decades. Originality/value: Summarizes relevant existing literature and adds a framework (network effects, how climate change shapes the development) for libraries making relevant decisions.